Review of Transnet National Ports Marine Concrete Infrastructure Asset Management and Maintenance - Isaacs, Benedict (Department of Civil Engineering, 2022)
The South African Ports are considered a key engine for the economic growth of the country for import and export trade as well as passenger ships. In order to provide such services, the ports' waterside / wet concrete assets are pivotal to the business as trade and travel are reliant on the availability of safe and well-maintained concrete assets. Transnet is a State-Owned Company (SOC), wholly owned by the Government of the Republic of South Africa and is the custodian of rail, ports, and pipelines. The asset management and maintenance of Transnet's infrastructure assets are, therefore, the cornerstone of delivering on their mandate as a SOC. Moreover, to deliver on their mandate, systematic, holistic, and integrated approaches to asset management and maintenance of their assets are imperative. This dissertation focuses on the Transnet National Ports Authority (TNPA) division. It has a very large asset base of Infrastructure, in particular its marine concrete infrastructure. Regulated by the National Ports Act 2005 (Act No. 12 of 2005), some of their core functions are the planning, provision, maintenance, and improvement of port infrastructure. This dissertation gives a background on the structure of the South African Ports and operations and the types and age of concrete structures within the ports. The study also critically assesses the existence of and the type of Infrastructure Asset Management & Maintenance (IAMM) systems currently in place for the Asset Management and Maintenance of TNPA's concrete infrastructure assets. The approach and methods of managing and assessing assets' condition and maintaining their existing concrete structures are reviewed to ascertain whether their asset management systems are aligned and conform to certain IAMM standards, codes, and guidelines. The Asset Maintenance Principles & Procedures (AMPP) document is also reviewed for its effectiveness in maintaining assets. In order to get a holistic idea of the extent of the possible shortcomings of TNPA's current maintenance and asset management strategies, other ports around the world with similar or the same concrete infrastructure are identified and assessed for commonalities and deviations from best practices. The research methodology used is qualitative using the analysis of existing text and literature as well as case studies of other ports as a source of data. The findings of the research show that although there are good maintenance systems and guidelines in place with some elements of asset management principles, an all encompassing civil infrastructure asset management framework for the marine concrete assets does not exists where the benefits of a properly implemented asset management framework can be realised. The research also shows that asset management is largely treated as a financial exercise with finance being the custodian of asset management. Recommendations are made for dealing with the shortcomings identified. Recommendations are also made for a more in-depth case study for the TNPA to conduct based on the findings of this dissertation.